2020
DOI: 10.1002/ca.23597
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional volumetric measurement of the aortic root compared to standard two‐dimensional measurements using cardiac computed tomography

Abstract: Introduction Two‐dimensional measurements are self‐evidently limited when seeking accurately to represent the three‐dimensional complexity of the aortic root. Volumetric measurement, therefore, seems an ideal alternative for a more accurate assessment. Materials and Methods We retrospectively analyzed 123 individuals undergoing cardiac computed tomography. We measured the dimensions of the sinuses of Valsalva using routine multiplanar short axis imaging. Three conventional two‐dimensional methods were applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Compared with the global threshold segmentation algorithm, the local threshold segmentation algorithm lost less blood vessel information, and the small and large blood vessels in the middle area were clearly separated [17,18]. It showed that the algorithm of this research was superior to the other two in segmentation effect and computing time, this is similar to the research results of Suzuki et al [19].…”
Section: Discussionsupporting
confidence: 76%
“…Compared with the global threshold segmentation algorithm, the local threshold segmentation algorithm lost less blood vessel information, and the small and large blood vessels in the middle area were clearly separated [17,18]. It showed that the algorithm of this research was superior to the other two in segmentation effect and computing time, this is similar to the research results of Suzuki et al [19].…”
Section: Discussionsupporting
confidence: 76%
“…1) (1,2), a nding con rmed by recent studies as well in adults (3)(4)(5). Despite this well-known feature, to the best of our knowledge the precise quantitative relationship between the lea ets size and shape has not yet been well de ned in large studies in pediatric populations, and studies in adults have used anatomic positioning of the lea ets as opposed to correlation of normal or abnormal origin of the coronary arteries (3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 91%
“…6 The space proximal to the skirt of tissue provided by the leaflets during diastole, which is distal to the plane of the virtual basal ring, hemodynamically is part of the left ventricular outflow tract. 6,7…”
Section: Anatomy Of the Normal Aortic Rootmentioning
confidence: 99%
“…When monitoring these patients, given the complexity of measuring the congenitally malformed aortic root, it may be helpful to measure cross-sectional areas or three-dimensional volumes. 7…”
Section: Normal Aortic Root Dimensionsmentioning
confidence: 99%